Application of remimazolam besylate combined with esketamine in outpatient colonoscopy in patients with hypertension - GUO Xiaoyang, LI Wei, HAO Zaijun (Xin yixue, 2025)
Objective To evaluate the efficacy and safety of remimazolam besylate combined with esketamine in outpatient colonoscopy in patients with hypertension. Methods A total of 48 hypertensive patients undergoing outpatient colonoscopy at the Ordos Central Hospital in 2023 were enrolled. The patients sequentially received 2% lidocaine 0.5 mg/kg and esketamine 0.15 mg/kg，followed by either remimazolam besylate 0.15-0.25 mg/kg（R group）or propofol 1-2 mg/kg（P group）for induction. Continuous infusion of remimazolam besylate at 1-2 mg/（kg·h）（R group）or propofol at 2-4 mg/（kg·h）（P group）was administered to maintain sedation. Differences between the two groups were observed and compared in terms of mean arterial pressure（MAP），heart rate（HR），respiratory rate（RR），and pulse oxygen saturation（SpO2），perioperative time indicators（induction time，operation time，resuscitation time and discharge time），and sedation indicators [bispectral index（BIS），the Modified Observer’s Assessment of Alertness/Sedation（MOAA/S）score，and the Ramsay sedation score]. Adverse events were also recorded. Results At 5 minutes after colonoscopy（T6），the MAP in the R group was higher than that in the P group [（95.7±2.8）mmHg vs.（92.5±3.0）mmHg，P < 0.05]. From the beginning to the end of the procedure（T3-T5），HR，RR，myocardial oxygen consumption，and BIS values were also higher in the R group（all P < 0.05）and all the above indicators remain within the normal range. Moreover，the R group perioperative minimum SpO2 is significantly higher than that of P group [（96.1±2.0）% vs.（94.0±2.4）%，P < 0.05]，and postoperative recovery quality score is higher than P group[（144.0±3.5）vs.（140.9±3.8），P < 0.05]，the rate of injection pain in R group is lower than P group（0% vs. 23.1 %，P < 0.05）. However，the induction [（4.4±1.2）s vs.（3.7±1.1）s] and resuscitation times [（4.4±1.2）s vs.（3.7±1.1）s] were prolonged in the R group（both P < 0.05）. There was no significant difference in the success rate of induction between the two groups（90.9% vs. 96.2%，P > 0.05）. Conclusions In outpatient colonoscopy for patients with hypertension，remimazolam besylate and propofol，when combined with esketamine，provide comparable sedative efficacy. However，remimazolam besylate is associated with less injection pain and more stable hemodynamics，suggesting it may serve as a preferable option in this population.